2023
DOI: 10.3390/su15043540
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Emotional Responses to Climate Change among Young People Worldwide: Differences Associated with Gender, Age, and Country

Abstract: Recent research has described concern and anxiety about climate change, especially among young people, but limited data are available looking at the responses of adolescents. Based on further analysis of an existing dataset that obtained survey responses from young people aged 16–25 in 10 different countries, this paper examines differences associated with gender and age, which are important predictors of vulnerability to the impacts of climate change. Gender differences were small but consistent, with female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Anxiety related specifically to climate change [36]. It often summarizes a negative emotional response to the impact of climate change, mainly characterized by an increase in anxiety (in the sense of a future-oriented concern) but sometimes including a constellation of emotions [81,86,87] referring to the perception of the existential risk and the potential loss of ontological security related to anthropogenic climate change [36]. It should not be considered primarily a disease or a presumable psychological impairment [87], because it is an understandable and appropriate reaction to the threat posed by climate change and it can be a potential resource as well [81,86,88].…”
Section: Climate Anxiety or Climate Change Anxiety Or Climate Change-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety related specifically to climate change [36]. It often summarizes a negative emotional response to the impact of climate change, mainly characterized by an increase in anxiety (in the sense of a future-oriented concern) but sometimes including a constellation of emotions [81,86,87] referring to the perception of the existential risk and the potential loss of ontological security related to anthropogenic climate change [36]. It should not be considered primarily a disease or a presumable psychological impairment [87], because it is an understandable and appropriate reaction to the threat posed by climate change and it can be a potential resource as well [81,86,88].…”
Section: Climate Anxiety or Climate Change Anxiety Or Climate Change-...mentioning
confidence: 99%
“…It often summarizes a negative emotional response to the impact of climate change, mainly characterized by an increase in anxiety (in the sense of a future-oriented concern) but sometimes including a constellation of emotions [81,86,87] referring to the perception of the existential risk and the potential loss of ontological security related to anthropogenic climate change [36]. It should not be considered primarily a disease or a presumable psychological impairment [87], because it is an understandable and appropriate reaction to the threat posed by climate change and it can be a potential resource as well [81,86,88]. It should be considered along a continuum, with only the higher levels of anxiety having the potential to increase the mental health burden [86], showing symptoms from mild (eg, occasional insomnia, restlessness, temporary paralysis when making decisions) to severe (eg, serious insomnia, difficulty maintaining functioning, self-destructive behaviors), and sometimes results in a clinically definable anxiety (Climate Anxiety Disorder) [88].…”
Section: Climate Anxiety or Climate Change Anxiety Or Climate Change-...mentioning
confidence: 99%
“…At the same time, communication about climate change is also relevant to adolescents' emotional well-being (Clayton et al, 2023). Recent research in large samples of adolescents from around the world found that most adolescents are worried or anxious about climate change, some of them extremely (Hickman et al, 2021).…”
Section: Climate Change Communication and Adolescents' Emotionsmentioning
confidence: 99%
“…But how can they do so? Learning about climate change and its harmful impacts is an inherently emotional process (Ojala, 2013), and it can have negative consequences for adolescents' emotional well-being (Clayton et al, 2023). Although preventing anxiety is not per se a goal of climate change communication, concern about provoking taxing levels of anxiety can present a barrier to communicating with youth about the topic (Baker et al, 2021;Verlie et al, 2021).…”
mentioning
confidence: 99%
“…Emotional maturity is a state or condition of reaching a level of maturity in emotional development, as the individual no longer displays emotional patterns that are appropriate for children [16]. Emotional maturity means the ability to think about emotions that helps to increase the ability to master or control them.…”
Section: Emotional Maturitymentioning
confidence: 99%